Safety and effectiveness of first line eflornithine for Trypanosoma brucei gambiense sleeping sickness in Sudan: cohort study. Issue 7646 (5th March 2008) - Priotto, Gerardo; Pinoges, Loretxu; Fursa, Isaac Badi; Burke, Barbara; Nicolay, Nathalie; Grillet, Guillaume; Hewison, Cathy; Balasegaram, Manica
Abstract : Objective To assess the safety and effectiveness of eflornithine as first line treatment for human African trypanosomiasis. Design Cohort study. Setting Control programme in Ibba, southern Sudan. Participants 1055 adults and children newly diagnosed with second stage disease in a 16 month period. Main outcome measures Deaths, severe drug reactions, and cure at 24 months. Results 1055 patients received eflornithine for 14 days (400 mg/kg/day in adults and 600 mg/kg/day in a subgroup of 96 children). Overall, 2824 drug reactions (2.7 per patient) occurred during hospital stay, 1219 (43.2%) after the first week. Severe reactions affected 138 (13.1%) patients (mainly seizures, fever, diarrhoea, and bacterial infections), leading to 15 deaths. Risk factors for severe reactions included cerebrospinal fluid leucocyte counts ≥100×10 9 /l (adults: odds ratio 2.6, 95% confidence interval 1.5 to 4.6), seizures (adults: 5.9, 2.0 to 13.3), and stupor (children: 9.3, 2.5 to 34.2). Children receiving higher doses did not experience increased toxicity. Follow-up data were obtained for 924 (87.6%) patients at any follow-up but for only 533 (50.5%) at 24 months. Of 924 cases followed, 16 (1.7%) died during treatment, 70 (7.6%) relapsed, 15 (1.6%) died of disease, 403 (43.6%) were confirmed cured, and 420 (45.5%) were probably cured. The probability of event free survival at 24 months was 0.88 (0.86 to 0.91). Most (65.8%, 52/79) relapses and disease related deaths occurred after 12 months. Risk factors for relapse included being male (incidence rate ratio 2.42, 1.47 to 3.97) and cerebrospinal fluid leucocytosis: 20-99×10 9 /l (2.35, 1.36 to 4.06); ≥100×10 9 /l (1.87, 1.07 to 3.27). Higher doses did not yield better effectiveness among children (0.87 v 0.85, P=0.981). Conclusions Eflornithine shows acceptable safety and effectiveness as first line treatment for human African trypanosomiasis. Relapses did occur more than 12 months after treatment. Higher doses in children were well tolerated but showed no advantage in effectiveness.